Low-platinum high-entropy alloy catalyst as well as preparation method and application thereof

Through a preparation method of a low-platinum high-entropy alloy catalyst, the problems of complex and costly preparation of high-entropy nanomaterials are solved, and the effect of rapid and efficient preparation of catalysts under normal temperature and pressure is achieved, and the catalytic performance and stability are significantly improved.

CN119747677APending Publication Date: 2025-04-04JIANGSU TOUTE INTELLIGENT TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411994189.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The preparation of existing high-entropy nanomaterials has problems such as high equipment, cumbersome preparation steps, limited support, and difficult to regulate component uniformity, which limits its application in catalytic reactions.

Method used

A low-platinum high-entropy alloy catalyst is used, which includes droplet coating of metal platinum precursor salt solution onto high-entropy alloy ultrasonic evaporation and drying, followed by laser treatment in a liquid phase environment, and finally obtaining a low-platinum high-entropy alloy catalyst by centrifugation and drying.

Benefits of technology

This method is simple to operate, low cost and mild reaction conditions. It can quickly and efficiently prepare high-entropy alloy nanocatalysts with arbitrary platinum load under normal temperature and pressure. Its performance is better than that of commercial Pt/C catalysts and remains stable during long-term cycle tests.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119747677A_ABST
    Figure CN119747677A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of high-entropy alloy catalysts, and discloses a low-platinum high-entropy alloy catalyst and a preparation method and application thereof. The preparation method comprises the following steps: dispensing a metal platinum precursor salt solution on a high-entropy alloy, and carrying out ultrasonic evaporation to dryness; uniformly grinding the dried mixture, and carrying out laser treatment in a liquid phase environment; and centrifuging the product subjected to laser treatment, adding ethanol and water, performing ultrasonic cleaning, removing supernate, and performing centrifugal drying to obtain the low-platinum high-entropy alloy catalyst. The method is simple to operate, low in cost, mild in reaction condition, rapid, efficient, environment-friendly and pollution-free. The technology provided by the invention can be used for preparing the high-entropy alloy nano-catalyst with any platinum loading capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of high entropy alloy catalysts, in particular to a low-platinum high entropy alloy catalyst and a preparation method and application thereof. Background Art

[0002] High entropy alloys (HEAs) refer to alloys with an entropy value of R>5, usually composed of a mixture of five or more different elements, with the atomic ratio of each element being 5%-35%. As a new type of material, HEAs have attracted much attention due to their complex surface chemical properties, excellent corrosion resistance, wide applicability, and synergistic effects between different elements. High entropy alloys have four unique effects: high entropy effect, hysteresis diffusion effect, lattice distortion effect, and cocktail effect. These effects make HEAs not only have strong stability as structural materials, but also have excellent performance as functional materials. These significant characteristics make HEAs a potential candidate for efficient electrocatalysts. However, the preparation of high entropy nanomaterials currently still has problems such as expensive equipment, cumbersome preparation steps, limited carriers, and difficult to control component uniformity, which limits the application of high entropy alloy nanomaterials in catalytic reactions. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a low-platinum high-entropy alloy catalyst and its preparation method and application. The preparation method of the present invention is simple to operate, low in cost, mild in reaction conditions, fast and efficient, and environmentally friendly and pollution-free. High-entropy alloy nanocatalysts with any platinum loading can be prepared under normal temperature and pressure conditions.

[0004] In order to achieve the above object, the present invention is implemented by the following technical solutions:

[0005] A method for preparing a low-platinum high-entropy alloy catalyst comprises the following steps:

[0006] The metal platinum precursor salt solution is dripped onto the high entropy alloy and ultrasonically evaporated to dryness; the evaporated mixture is ground evenly and laser treated in a liquid phase environment; the laser-treated product is centrifuged and ultrasonically cleaned by adding ethanol and water, and the supernatant is removed and centrifuged and dried to obtain a low-platinum high entropy alloy catalyst;

[0007] The high entropy alloy includes four or more of copper, chromium, tin, iron, cobalt, nickel, zinc, manganese, molybdenum, magnesium, aluminum, titanium, vanadium, tantalum, tungsten, zirconium, niobium, yttrium, etc.; the metal platinum precursor salt includes one or more of chlorides, sulfates, phosphates, and nitrates.

[0008] Furthermore, the laser processing power density is 10 5 ~10 9 W / cm 2, frequency 1~80 kHz, laser processing time is 1~3h; the laser wavelength range covers ultraviolet, visible and infrared light, and the laser pulse width is 4~6ns.

[0009] Furthermore, the solvent used in the metal platinum precursor salt solution includes any one of ethanol, methanol, water, acetone, and isopropanol.

[0010] Furthermore, the ultrasonic evaporation is to set the temperature of the ultrasonic machine to 60-70° C. and stir with ultrasound until the solution is evaporated to dryness.

[0011] Furthermore, the liquid phase environment includes any one of alkanes, ethanol, water, and methanol.

[0012] Furthermore, the centrifugal speed is 12000-20000 rpm, and the time is 10-30 min.

[0013] Furthermore, the drying is vacuum drying or freeze drying, the vacuum drying temperature is 30-50°C, the time is 11-13 hours, and the freeze drying time is 18-22 hours.

[0014] Furthermore, the high entropy alloy is in the form of powder particles of 1 to 30 μm, and the mass ratio of the high entropy alloy to the metal platinum precursor salt is 1:0.1 to 0.3.

[0015] A method for preparing a low-platinum high-entropy alloy catalyst comprises the following steps:

[0016] (1) Dissolve the metal platinum precursor salt in a solvent, then drop-coat it on the high entropy alloy and ultrasonically evaporate it to dryness. The solvents involved include but are not limited to ethanol, methanol, water, acetone, isopropanol, etc. The high entropy alloy is a powder particle of 1 to 30 μm. The ultrasonic evaporation is performed by setting the temperature of the ultrasonic machine to 65°C and stirring the solution with ultrasound until it is evaporated to dryness.

[0017] (2) The mixture evaporated in step (1) was ground evenly, then transferred to a container (beaker), and laser treated in a liquid phase environment. The laser treatment parameters involved were a power density of 10 5 ~10 9 W / cm 2 , frequency 1 Hz-80 kHz; laser wavelength range covers ultraviolet, visible and infrared light. The liquid phase environment involved includes but is not limited to various alkanes, ethanol, water, methanol, etc.

[0018] (3) The product after laser treatment is placed in a test tube, centrifuged, and ultrasonically cleaned by adding ethanol and water. Then, the upper layer solution is placed in another clean test tube, and the low-platinum high-entropy alloy catalyst is obtained after centrifugal drying. The speed of the two centrifuges is 12000-20000 rpm, and the time is 10-30 min. The drying is vacuum drying or freeze drying, and the vacuum drying temperature is 30-50°C, the time is 12 hours, and the freeze drying time is 20 hours.

[0019] Furthermore, the high entropy alloy involved in step (1) has an entropy value R>5, and is composed of four or five elements selected from the group consisting of copper, chromium, tin, iron, cobalt, nickel, zinc, manganese, molybdenum, magnesium, aluminum, titanium, vanadium, tantalum, tungsten, zirconium, niobium, and yttrium; the precursor salt of metal platinum includes but is not limited to chlorides, sulfates, phosphates, and nitrates.

[0020] Any platinum loading can be achieved on any high entropy alloy substrate by adjusting the content of platinum precursor salt and the components of high entropy alloy. The present invention achieves the effect of low platinum by changing the amount of platinum precursor salt. The platinum loading of the obtained catalyst is 5-40%.

[0021] The present invention also provides a low-platinum high-entropy alloy catalyst, which is prepared by the above preparation method.

[0022] The present invention also provides the use of the low-platinum high-entropy alloy catalyst in an electrocatalytic reaction.

[0023] Beneficial Effects

[0024] The present invention simplifies the cumbersome steps of synthesizing high-entropy nanocatalysts at present, and realizes the synthesis of low-platinum-loaded high-entropy catalysts at room temperature through a simple one-step laser ablation method, thereby reducing the amount of precious metals used to save costs. The technology of the present invention can realize the loading of any platinum loading on any high-entropy alloy substrate by regulating the content of the platinum precursor salt and the components of the high-entropy alloy. In a specific embodiment, a high-entropy alloy composed of transition metal elements such as Mo, W, Cr with half-empty d orbitals and Fe, Co, Ni with a large number of paired d electrons is selected to promote the electron transfer of the catalyst and the adsorption and desorption of intermediates. The catalyst prepared by this method has a high conductivity at 10 mA cm -2 The overpotential η is only 26mV, which is much better than the commercial Pt / C catalyst. Thanks to the hysteresis diffusion effect brought by the high entropy alloy, the performance of the catalyst does not decay after 1500 cycles of CV cycle test. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Schematic diagram of the laser synthesis process of low-platinum high-entropy alloy nanocatalysts;

[0026] Figure 2A is a comparison chart of the hydrogen evolution reaction (HER) performance of the catalysts prepared in Example 1 and Comparative Example 1 under 1M KOH conditions, Figure 2 B is a stability test diagram of the catalyst prepared in Example 1;

[0027] Figure 3 The catalytic effect of the catalyst of Comparative Example 2 is shown in Figure A, wherein Figure A is a comparison of the hydrogen evolution reaction (HER) performance of the catalysts prepared in Example 1 and Comparative Example 2 under 1M KOH conditions, and Figure B is a stability test diagram of the catalyst prepared in Comparative Example 2;

[0028] Figure 4 The performance comparison diagram of low-platinum high-entropy nanocatalyst and commercial Pt / C 20% in hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) under 1M KOH conditions; Figure A is the low-platinum high-entropy nanocatalyst prepared in Example 1 (named HEA-20%Pt) and Figure B is the low-platinum high-entropy nanocatalyst (HEA-10%Pt) prepared in Example 2;

[0029] Figure 5 It is the full range XPS energy spectrum of the low-platinum high-entropy nanocatalyst (HEA-20%Pt) prepared in Example 1 and Pt-4f, wherein Figure A is the full range XPS energy spectrum and Figure B is the XPS energy spectrum of Pt-4f. DETAILED DESCRIPTION

[0030] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, but this should not be construed as limiting the scope of protection of the present invention.

[0031] Example 1

[0032] The present invention provides a method for preparing a low-platinum high-entropy alloy catalyst, comprising the following steps:

[0033] (1) Take 300 mg of HEA powder (R>5, equimolar ratio of FeCoNiCrMo, particle size about 25 μm) in a 5 mL centrifuge tube and mix according to HEA:H 2 PtCl 6 =1:0.2 mass ratio of H 2 PtCl 6 Dissolve in ethanol, then drop onto HEA powder, and move to an ultrasonic machine. Set the temperature of the ultrasonic machine to 65°C, the ultrasonic power to 300-350W, the frequency to 40KHz, the time to 10-20min, and ultrasonicate until the solution is evaporated.

[0034] (2) The mixture in step (1) was transferred to a mortar with a weighing spoon for grinding until no solid lumps were left. The powder was then poured onto a tin foil with the aid of a weighing spoon and transferred into a beaker. About 20 mL of n-hexane was added using a pipette. The precursor material was laser scanned and ablated using a nanosecond pulse laser with a pulse width of 5 ns. A top-down ablation strategy was adopted (the laser path was from top to bottom, and the focus was concentrated at the bottom of the beaker). The average laser power density was set to 2 × 10 5 W / cm 2 , the frequency is 20kHz, the processing time is 2h, and the laser wavelength belongs to the infrared band.

[0035] (3) The product after laser treatment was placed in a 5 mL test tube, centrifuged and added with ethanol and water for ultrasonic cleaning 2-3 times. The centrifugal speed was set to 12000 rpm for 25 min. After cleaning, 2 mL of ethanol was added to the test tube and ultrasonic cleaning was performed. The cleaning method was to place the catalyst in a 5 mL centrifuge tube, add 1 mL of ethanol and 1 mL of deionized water, and place it in an ultrasonic cleaning machine for ultrasonic cleaning. The catalyst was then allowed to stand and the upper colloidal solution was placed in another clean test tube. The catalyst was centrifuged and vacuum freeze-dried to obtain a low-platinum high-entropy alloy nanocatalyst. The vacuum freeze-drying temperature was -20~-30°C and the time was 8 h.

[0036] The ICP test results of the catalyst showed that the mass fraction of platinum was 21.1wt%, which was consistent with the feed ratio. The obtained low-platinum high-entropy alloy nanocatalyst was tested for hydrogen evolution reaction performance under 1M KOH conditions. The results are as follows: Figure 2 As shown in A, due to the synergistic effect of atoms in the high entropy alloy, at 10 mA cm -2 The overpotential η is only 26mV. Thanks to the hysteresis diffusion effect brought by the high entropy alloy, the catalyst has no performance degradation after 1500 cycles of CV test ( Figure 2 B).

[0037] Comparative Example 1

[0038] The difference between Comparative Example 1 and Example 1 is that no platinum precursor salt is introduced in Comparative Example 1, and specifically comprises the following steps:

[0039] (1) 300 mg of HEA powder (R>5, equimolar ratio of FeCoNiCrMo, particle size of about 25 μm) was placed in a beaker, and about 20 mL of n-hexane was added using a pipette. The precursor material was laser scanned and ablated using a nanosecond pulse laser with a pulse width of 5 ns. A top-down ablation strategy was adopted (the laser path was from top to bottom, and the focus was concentrated at the bottom of the beaker). The average laser power density was set to 2×10 5 W / cm 2 , the frequency is 20 kHz, the processing time is 2h, and the laser wavelength belongs to the infrared band.

[0040] (2) The laser-treated product was placed in a 5 mL test tube, centrifuged, and ultrasonically cleaned with ethanol and water for 2-3 times. The centrifugal speed was set to 12,000 rpm for 25 min. After cleaning, 2 mL of ethanol was added to the test tube and ultrasonicated. The solution was then allowed to stand and the upper colloidal solution was placed in another clean test tube. The high entropy alloy nanocatalyst was obtained after centrifugation and vacuum freeze-drying.

[0041] The obtained high entropy alloy nanocatalyst was tested for hydrogen evolution reaction performance under 1M KOH conditions. The results are as follows Figure 2 As shown in A, at 10mAcm -2 The overpotential η under the condition is 340 mV, which indicates that the high entropy alloy itself has almost no catalytic effect on the hydrogen evolution reaction. Compared with Example 1, it shows that the active sites of the hydrogen evolution reaction are located on the platinum nanoparticles supported on the high entropy alloy.

[0042] Comparative Example 2

[0043] The difference between Comparative Example 2 and Example 1 is that the drip coating step is not performed, and the chloroplatinic acid powder and the HEA metal powder are directly ground and mixed uniformly, which specifically includes the following steps:

[0044] (1) Take 300 mg of HEA powder (R>5, equimolar ratio of FeCoNiCrMo, particle size about 25 μm) and place it in a mortar. 2 PtCl 6 =1:0.2 mass ratio of H 2 PtCl 6 After grinding the two materials evenly, they were placed in a beaker. About 20 mL of n-hexane was added using a pipette. The precursor material was laser scanned and ablated using a nanosecond pulse laser with a pulse width of 5 ns. A top-down ablation strategy was adopted (the laser path was from top to bottom, and the focus was concentrated at the bottom of the beaker). The average laser power density was set to 2×10 5 W / cm 2 , the frequency is 20 kHz, the processing time is 2h, and the laser wavelength belongs to the infrared band.

[0045] (2) The laser-treated product was placed in a 5 mL test tube, centrifuged, and ultrasonically cleaned with ethanol and water for 2-3 times. The centrifugal speed was set to 12,000 rpm for 25 min. After cleaning, 2 mL of ethanol was added to the test tube and ultrasonicated. The solution was then allowed to stand and the upper colloidal solution was placed in another clean test tube. The high entropy alloy nanocatalyst was obtained after centrifugation and vacuum freeze-drying.

[0046] The obtained high entropy alloy nanocatalyst was tested for hydrogen evolution reaction performance under 1M KOH conditions. The results are as follows Figure 3As shown in A, at 10mAcm -2 The overpotential η under the condition is 50mV, which is lower than the catalytic effect in Example 1. At the same time, under 1500 CV cycle tests, 10mAcm -2 The overpotential η under the condition of irradiation increased by 13.6mV, and the stability of the catalyst decreased. This is due to the direct grinding without the step of drip coating and evaporation, which leads to weak adsorption of the reactant Pt and the high entropy alloy and poor laser effect. The drip coating and evaporation step brings about a "sticky" effect between Pt and the high entropy alloy, so that the two are in full contact during the laser action, thereby promoting the bonding between Pt and the high entropy alloy in the catalyst.

[0047] Example 2

[0048] The difference between Example 2 and Example 1 is that the method comprises the following steps:

[0049] (1) Take 200 mg of HEA powder (R>5, equimolar ratio of NiMoCrFeW, particle size about 25 μm) in a 5 mL centrifuge tube and mix according to HEA:H 2 PtCl 6 =1:0.1 mass ratio of H 2 PtCl 6 Dissolve in isopropanol, then drop onto HEA powder, and move to an ultrasonic machine. Set the temperature of the ultrasonic machine to 65°C, the ultrasonic power to 300-350W, the frequency to 40KHz, the time to 10-20min, and ultrasonicate until the solution is evaporated.

[0050] (2) The mixture in step (1) was transferred to a mortar with a weighing spoon for grinding until no solid lumps were left. The powder was then poured onto a tin foil with the aid of a weighing spoon and transferred into a beaker. About 20 mL of ethanol was added using a pipette. The precursor material was laser scanned and ablated using a nanosecond pulse laser with a pulse width of 5 ns. A top-down ablation strategy was adopted (the laser path was from top to bottom, and the focus was concentrated at the bottom of the beaker). The average laser power density was set to 2 × 10 5 W / cm 2 , the frequency is 10kHz, the processing time is 2h, and the laser wavelength belongs to the infrared band.

[0051] (3) The product after laser treatment was placed in a 5 mL test tube, centrifuged and added with ethanol and water for ultrasonic cleaning 2-3 times. The centrifugal speed was set to 12000 rpm for 25 min. After cleaning, 2 mL of ethanol was added to the test tube and ultrasonic cleaning was performed. The cleaning method was to place the catalyst in a 5 mL centrifuge tube, add 1 mL of ethanol and 1 mL of deionized water, and place it in an ultrasonic cleaning machine for ultrasonic cleaning. Then, the upper colloidal solution was placed in another clean test tube, centrifuged and placed in a 45 °C vacuum drying oven for 12 h to obtain a low-platinum high-entropy alloy nanocatalyst.

[0052] The obtained low-platinum high-entropy alloy nanocatalyst was tested for hydrogen evolution reaction performance under 1M KOH conditions. The results are as follows Figure 4 As shown in A, at 10mAcm -2 The overpotential η under the condition is almost consistent with the performance of commercial Pt / C20%. The ICP results show that the mass fraction of platinum loaded on the high entropy alloy is 10.7 wt %, which means that the catalyst prepared by the patented method can reduce the amount of Pt while its performance is comparable to that of commercial catalysts, which is equivalent to reducing the cost of the catalyst. Figure 5 As shown in the figure, the XPS results further illustrate the bonding between Pt in the catalyst and the elements in the high entropy alloy, and the Pt-Pt bond (4f 7 / 2 =71.2eV), the Pt element in the catalyst shifted negatively by 0.1eV ( Figure 5 B), this is because Pt has a higher electronegativity than the elements in HEA, and the electrons shift toward the Pt element during bonding, which also confirms the bonding between HEA and Pt.

[0053] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and the scope of protection of the present invention is defined by the attached claims, description and their equivalents.

Claims

1. A method for preparing a low-platinum high-entropy alloy catalyst, characterized in that: The following steps are involved: The metal platinum precursor salt solution is dripped onto the high entropy alloy and ultrasonically evaporated to dryness; the evaporated mixture is ground evenly and laser treated in a liquid phase environment; the laser-treated product is centrifuged and ultrasonically cleaned by adding ethanol and water, and the supernatant is removed and centrifuged and dried to obtain a low-platinum high entropy alloy catalyst; The high entropy alloy includes four or more of copper, chromium, tin, iron, cobalt, nickel, zinc, manganese, molybdenum, magnesium, aluminum, titanium, vanadium, tantalum, tungsten, zirconium, niobium, yttrium, etc.; the metal platinum precursor salt includes one or more of chlorides, sulfates, phosphates, and nitrates.

2. The method for preparing a low-platinum high-entropy alloy catalyst according to claim 1, characterized in that: The laser processing power density is 10 5 ~10 9 W / cm 2 , frequency 1~80 kHz, laser processing time is 1~3h; the laser wavelength range covers ultraviolet, visible and infrared light, and the laser pulse width is 4~6ns.

3. The method for preparing a low-platinum high-entropy alloy catalyst according to claim 1, characterized in that: The solvent used in the metal platinum precursor salt solution includes any one of ethanol, methanol, water, acetone and isopropanol.

4. The method for preparing a low-platinum high-entropy alloy catalyst according to claim 1, characterized in that: The ultrasonic evaporation is to set the temperature of the ultrasonic machine to 60-70° C. and stir the solution with ultrasound until the solution is evaporated to dryness.

5. The method for preparing a low-platinum high-entropy alloy catalyst according to claim 1, characterized in that: The liquid phase environment includes any one of alkanes, ethanol, water and methanol.

6. The method for preparing a low-platinum high-entropy alloy catalyst according to claim 1, characterized in that: The centrifugal speed is 12000-20000 rpm, and the time is 10-30 min.

7. The method for preparing a low-platinum high-entropy alloy catalyst according to claim 1, characterized in that: The drying is vacuum drying or freeze drying, the vacuum drying temperature is 30-50° C., the time is 11-13 hours, and the freeze drying time is 18-22 hours.

8. The method for preparing a low-platinum high-entropy alloy catalyst according to claim 1, characterized in that: The high entropy alloy is in the form of powder particles with a size of 1 to 30 μm, and the mass ratio of the high entropy alloy to the metal platinum precursor salt is 1:0.1 to 0.

3.

9. A low-platinum high-entropy alloy catalyst, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the low-platinum high-entropy alloy catalyst according to claim 9 in an electrocatalytic reaction.